Linguistic Errors of Indonesian Air Transportation Hoax - Pinem, Yune Andryani (Lingua Cultura, 2022)
The research was to find out linguistics’ indicators of errors found in the body content of false news discourse mingling around air transportation issues that appeared 2-years before the presidential election in 2019. The qualitative research used hoax discourse from the turnbackhoax.com collection. Errors found in discourse were later generated according to linguistics’ domain in Dulay et al., as well as additional spelling errors and surface strategy taxonomy. Toward false news (n=44) found in the data source, errors majorly emerge in newly ungrammatical word formation with omission process equitably distributed in all linguistics’ domains. Errors in phonology portray localization in several dialects in Indonesia, while errors in morphology and syntax appear for language economy purposes. Primarily affected, lexicon and semantics is the domain with the most variant of surface structure errors (n=4). This is relevant to the hoax spread’s intended purpose to deceive the audience by modifying words in originally true news to give different content meanings. Omission resulting in word shortening in the form of blending and clipping with 98% occurrences is popularly used by millennials with a medium level of media literacy to communicate in the digital society environment. To enhance relatedness in readers’ thoughts and feelings, explain errors that deliberately happened in pragmatics and spelling. Being familiar with these indicators can alert the public to question a post’s credibility, thus encouraging the urge for clarification.